PENINGKATAN HASIL BELAJAR PKn MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE (NHT) PADA SISWA KELAS IV SD NEGERI 006 TRI MULYA JAYA KECAMATAN UKUI - Nurya’adi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes of fourth-grade students in Civics at SD Negeri 006 Tri Mulya Jaya, Ukui District. This condition is evidenced by the average Civics learning score of only 55, with student learning mastery reaching merely 50%. This research employed a classroom action research design aimed at improving students’ Civics learning outcomes through the implementation of the cooperative learning model Numbered Heads Together (NHT). The study was conducted over two cycles, utilizing data on teacher and student activities as well as students’ Civics learning outcomes as the primary sources of analysis. The results of the study indicate a consistent improvement in both learning outcomes and classroom activities across each cycle. Teacher activity increased from 47% in Cycle I Meeting I to 56% in Cycle I Meeting II, then rose to 69% in Cycle II Meeting I and 73% in Cycle II Meeting II. Similarly, student activity improved from 50% in Cycle I Meeting I to 57% in Cycle I Meeting II, increased to 65% in Cycle II Meeting I, and reached 82% in Cycle II Meeting II. In terms of learning outcomes, the average student score increased from 55 in the initial assessment (UH I) to an average of 79, and further improved to an average score of 80 in the second cycle. These findings demonstrate that the implementation of the NHT cooperative learning model effectively enhances both student engagement and Civics learning outcomes at the elementary school level.